Tunings on theater of word. Notes on Víctor M. Díez and Ildefonso Rodríguez’s poetry - Trabado Cabado, José Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper aims to study the Ildefonso Rodríguez´s and Víctor M. Díez poetics. Both are stemmed in the strong influence of jazz on poetry. They share a way of facing the moment of creation as a sort of improvisation. Each of them uses his own formal devices as fragmented texts, broken syntax and a wide range of references to other languages such as theater, cinema in order to deconstruct everyday speech. Both of them deals with the problem of identity: Ildefonso builds up a kind of ex-centered self while Victor´s poetry is based on we can call defacement of self.